Goresan Imaji dan Narasi Budaya Masyarakat Kawasan Candi - Wahyu Purwiyastuti (Lembaran Sejarah, 2019)
The Cetho people who live on the slopes of Mount Lawu Karanganyar, have images and cultural narratives. Historical social reality is represented through temple artifacts, house architecture, community service activities, social gathering, etc. This article is a description of the imagination and cultural narratives of the people in the form of oral and written. The results of the culture are packaged in the form of historiography. This article uses qualitative research methods with a cultural history approach. Research, observation and assistance have been carried out since 2011 to 2017. Literacy culture has not been implemented based on standard needs. Therefore, historiographic production is still minimal. The Cetho temple community creates more oral culture. The cultural literacy movement launched by the Ministry of Education and Culture in 2017 has not been fully appreciated. Academics hold a “Live in” program to improve literacy culture. Students write historiography during the “Live in” program in the Cetho temple area. Collaboration and synergy between the community, schools, local government officials, and academics is useful to open opportunities for local cultural literacy education in the national interest.